Effects of high-intensity anaerobic exercise on the scavenging activity of various reactive oxygen species and free radicals in athletes - Sawada, Y.; Ichikawa, H.; Ebine, N.; Minamiyama, Y.; Alharbi, A. A. D.; Iwamoto, N.; Fukuoka, Y. (Nutrients, 2023)
High-intensity exercise in athletes results in mainly the production of excess reactive oxygen species (ROS) in skeletal muscle, and thus athletes should maintain greater ROS scavenging activity in the body. We investigated the changes in six different ROS-scavenging activities in athletes following high-intensity anaerobic exercise. A 30-s Wingate exercise test as a form of high-intensity anaerobic exercise was completed by 10 male university track and field team members. Blood samples were collected before and after the exercise, and the ROS-scavenging activities (OH•, O2•-, 1O2, RO• and ROO•, and CH3•) were evaluated by the electron spin resonance (ESR) spin-trapping method. The anaerobic exercise significantly increased RO• and ROO• scavenging activities, and the total area of the radar chart in the ROS-scavenging activities increased 178% from that in pre-exercise. A significant correlation between the mean power of the anaerobic exercise and the 1O2 scavenging activity was revealed (r = 0.72, p < 0.05). The increase ratio in OH• scavenging activity after high-intensity exercise was significantly greater in the higher mean-power group compared to the lower mean-power group (n = 5, each). These results suggest that (i) the scavenging activities of some ROS are increased immediately after high-intensity anaerobic exercise, and (ii) an individual`s OH• scavenging activity responsiveness may be related to his anaerobic exercise performance. In addition, greater pre-exercise 1O2 scavenging activity might lead to the generation of higher mean power in high-intensity anaerobic exercise.